Bronchoscopic View of an Intracavitary Aspergilloma - Sarkar, Nirmal Kanti; Bali, Abhishek (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Aspergilloma, also known as mycetoma or fungal ball, is caused by pulmonary involvement of Aspergillus species in a pre-existing lung cavity as evidenced by air crescent sign in computed tomography scan of chest. Direct visualization of aspergilloma in cavity is a rare bronchoscopic finding. J Bangladesh Coll Phys Surg 2025; 43: 186-187